Properties of resonance circuits of radio electronics - Lebedev, P.F.; Milutchenko, I.A. (Radiotekhnika, 2018)
The article gives new ideas on the transformation of resonance chains in the frequency domain using the structural law. The analogy of the equivalence of bipolar resistive structures with three elements and R, L, C chains is shown. The work is of interest in digital modeling.